Accelerated discovery and testing of Fe–Co–Cr–Ni–Mo ferrous medium-entropy alloys: advanced in-situ alloying via direct energy deposition - Jae Heung Lee; Ji Yeong Lee; Bon Woo Koo; Dae-Kyeom Kim; Jungwan Lee; Eun Seong Kim; Hyojeong Ha; Taek-Soo Kim; Hyoung Seop Kim (Journal of Materials Research and Technology)
Traditional trial-and-error alloy design methods have reached their limitations due to the growing complexity of alloy systems such as high-entropy alloys (HEAs). In-situ alloying through direct energy deposition (DED) using elemental powders has been introduced as a high-throughput synthesis method for HEA design. However, large melting point differences can cause unmelted particle issues, limiting its applicability to complex alloy systems such as FeCoCrNiMo ferrous medium-entropy alloys (FeMEAs). In this paper, an advanced in-situ alloying method is proposed to facilitate accelerated alloy discovery and testing (ADAT) for FeCoCrNiMo FeMEA systems by using multiple pre-alloyed powders. Three types of powders - Fe65Co20Mo15 (at%), Fe33.4Cr33.3Ni33.3 (at%), and Fe64Co29Cr7 (at%) - were designed and fabricated, reducing the melting point differences while preserving the ability to synthesize a wide range of compositions. A total of 27 FeCoCrNiMo FeMEA samples with different compositions were successfully fabricated via in-situ alloying. Both the compositional homogeneity and precise adherence to the target composition were achieved, underscoring the excellence of the proposed method. In addition, composition-structure-property linkages were constructed over a wide range of compositions, based on the analysis results of the high-throughput synthesized samples. The #4 (Fe53.9Co16.8Cr11.7Ni11.5Mo6.0) and #7 (Fe52.9Co16.1Cr12.8Ni12.5Mo5.6) samples exhibited the highest hardness levels while maintaining an FCC single-phase structure. These selected compositions were fabricated in bulk samples, and tensile testing of bulk samples revealed that Fe53.9Co16.8Cr11.7Ni11.5Mo6.0 demonstrated superior tensile properties with improved strain hardening behavior, identifying it as optimized composition. This study offers valuable insights to advance the development of novel alloys through high-throughput synthesis methods.